Evaluation of Changes of Lungs in Asthmatic Rats Treated with Aqueous and Non Aqueous Extract of Clerodendrum Serratum and Theophylline - Dr.K.K. Senthil Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The aim of the present work is help the researchers for the development of an alternative methods rather than inhalers and oral anti asthmatic drugs for the treatment of asthma and COPD which will minimize the complication. Many plants obtained from the natural source play a significant role in the health care system. Literature survey on herbal drugs has shown significant anti asthmatic activity which has not shown any remarkable side effect. The pharmacological mechanism which the phyto constituents producing the anti asthmatic activity are not clearly understood till date. The several herbal formulation have derived from the Ayurveda, traditional system of Indian medicine and its additional system of medicine, yet to be scientifically validated that they have exhibited pharmacological action against Asthmatic. Only less number of scientific data of traditional medicines is available for the treatment of Asthmatic.